A randomized, controlled, double-blind, crossover trial of zonisamide in myoclonus-dystonia. (3rd May 2016) - Hainque, Elodie; Vidailhet, Marie; Cozic, Nathalie; Charbonnier-Beaupel, Fanny; Thobois, Stéphane; Tranchant, Christine; Brochard, Vanessa; Glibert, Gérald; Drapier, Sophie; Mutez, Eugénie; Doe De Maindreville, Anne; Lebouvier, Thibaud; et al.
Abstract : Objective: To evaluate the efficacy and safety of zonisamide in patients with myoclonus-dystonia. Methods: We conducted a randomized, double-blind, placebo-controlled crossover trial of zonisamide (300 mg/d) in 24 patients with myoclonus-dystonia. Each treatment period consisted of a 6-week titration phase followed by a 3-week fixed-dose phase. The periods were separated by a 5-week washout period. The co–primary outcomes were action myoclonus severity (section 4 of the Unified Myoclonus Rating Scale [UMRS 4]) and myoclonus-related functional disability (UMRS 5). Secondary outcomes included dystonia severity, assessed with the movement and disability subscales of the Burke-Fahn-Marsden-Dystonia Rating Scale (BFM), the Clinical Global Impression–Improvement scale (CGI), and safety measures. Wilcoxon signed-rank tests for paired data were used to analyze treatment effects. Results: Twenty-three patients (11 men, 12 women) were analyzed in the intention-to-treat analysis. Zonisamide significantly improved both action myoclonus (median improvement [95% confidence limits] −5 [−9.25 to −1.44], p = 0.003) and myoclonus-related functional disability (median improvement [95% confidence limits] −2 [−2.58 to −2.46], p = 0.007) compared to placebo. Zonisamide also significantly improved dystonia (BFM movement) compared to placebo (median improvement [95% confidence limits] −3 [−8.46 to 0.03], p = 0.009). No difference was found between zonisamide and placebo with respect to the CGI (median improvement [95% confidence limits] −1 [−1.31 to 0.09], p = 0.1). Zonisamide was well-tolerated. Conclusions: Zonisamide is well-tolerated and effective on the motor symptoms of myoclonus-dystonia. Classification of evidence: This study provides Class I evidence that zonisamide improves myoclonus and related disability in patients with myoclonus-dystonia.